Cooperation in science and innovation between Latin America and the European Union - Simone Belli; Jenny Morín Nenoff (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Since the launch of the Strategic Partnership in 1999, the European Union and Latin America and the Caribbean countries have formed a political agenda for bi-regional dialogues. In this study we present a comprehensive analysis of the political and the technical levels of the bi-regional cooperation. The analytical approach that we develop to study bi-regional STI relations is based on a thorough examination of the legal foundations of the EU, which allows for assessment of the possibilities and limits. We identify the LAC dimension of the EU's scientific policies, offering an overview of the challenges and achievements of bi-regional STI cooperation. These are derived from an analysis of limitations in the current cooperation programs. Additionally, the latter is being connected to the discussion of support needs that are raised by the survey participants. We provide a list of suggestions for further instruments and activities, as the main motive is to strengthen and widen the cooperation with concrete actions.
Keywords: 650; EU policies; EU-LAC cooperation; innovation; LAC policies; scientific policies